Problem solving and collaborative involvement among adolescents with spinal cord injury and their caregivers - Clark, Olivia E.; Rivelli, Anne L.; Mroczkowski, Alison L.; Espino, Susan Ryerson; Kelly, Erin Hayes; Vogel, Lawrence C.; Zebracki, Kathy (Frontiers in Rehabilitation Sciences, 2023)
Objective To determine the relationship between constructive adolescent problem solving (positive problem-solving orientation and rational problem-solving style) and caregiver problem solving and collaborative involvement with primary caregiver among adolescents with spinal cord injuries (SCIs). Positive constructive adolescent problem solving was hypothesized to be predicted by more effective caregiver problem solving and higher collaborative involvement. Methods Participants in this cross-sectional study were 79 adolescent and primary caregiver dyads recruited from a pediatric rehabilitation care system in North America. All participants completed a standardized problem-solving instrument and adolescent participants completed an adapted measure of collaborative parent involvement. Results More effective caregiver problem solving and adolescent perceptions of more collaboration with caregivers around SCI care were significantly associated with higher positive problem-solving orientation and higher rational problem-solving style among adolescents. Conclusions Results underscore the importance of caregiver problem-solving skills and their collaboration with adolescents with SCI when addressing care needs. Clinically, findings highlight opportunities for parent involvement and skill-building as an important factor of rehabilitation for adolescents with SCI.